Performance analysis on bipolar PWM strategies for single phase quasi-Z-source fed seven level modified cascaded H-bridge inverter with asymmetric switched-inductor cell - Meenalochani, K; Shanthi, B; R.Balamurugan, C; Prem sunder, G (International Journal of Engineering and Technology, 2018)
Multilevel inverters are adopted for high power applications due to its lower harmonic distortion and reduced device voltage stress which also permit to use the renewable energy resources effectively. This paper presents performance study of various PWM strategies for single phase Quasi-Z-source fed seven level Modified Cascaded H-Bridge Inverter with asymmetric switched-inductor cell. Simulation using MATLAB-SIMULINK is performed with bipolar multi-carrier PD, APOD, POD PWM techniques with sine wave reference and trapezoidal reference for the chosen Quasi-Z-source modified CHB MLI. This paper suggests notably improved results to yield great boosting in root mean square value of the fundamental component with enriched voltage enhancement techniques along with suitable PWM strategy.